2003
DOI: 10.1074/jbc.m211050200
|View full text |Cite
|
Sign up to set email alerts
|

The PDZ-binding Chloride Channel ClC-3B Localizes to the Golgi and Associates with Cystic Fibrosis Transmembrane Conductance Regulator-interacting PDZ Proteins

Abstract: . ClC-3A resides in late endosomes where it serves as an anion shunt during acidification. We show here that the ClC-3B PDZ-binding isoform resides in the Golgi where it co-localizes with a small amount of the other known PDZ-binding chloride channel, CFTR (cystic fibrosis transmembrane conductance regulator). Both channel proteins bind the Golgi PDZ protein, GOPC (Golgi-associated PDZ and coiled-coil motif-containing protein). Interestingly, however, when overexpressed, GOPC, which is thought to influence tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
115
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(120 citation statements)
references
References 36 publications
4
115
0
Order By: Relevance
“…Two other members of this family, ClC-3 and ClC-5, have been localized to endosomal compartments (39 -41). However, unlike ClC-2, which is thought to mediate its primary function at the cell surface, both ClC-3 and ClC-5 are stably expressed in endomembranes where they are thought to regulate the function of this organelle (39,41). Hence, the molecular components mediating localization and trafficking of ClC-3 and ClC-5 may be distinct from those mediating ClC-2 trafficking.…”
Section: Discussionmentioning
confidence: 92%
“…Two other members of this family, ClC-3 and ClC-5, have been localized to endosomal compartments (39 -41). However, unlike ClC-2, which is thought to mediate its primary function at the cell surface, both ClC-3 and ClC-5 are stably expressed in endomembranes where they are thought to regulate the function of this organelle (39,41). Hence, the molecular components mediating localization and trafficking of ClC-3 and ClC-5 may be distinct from those mediating ClC-2 trafficking.…”
Section: Discussionmentioning
confidence: 92%
“…Overexpressed CAL decreases the half-life of mature CFTR by facilitating lysosomal degradation to reduce its plasma membrane expression (Cheng et al, 2002(Cheng et al, , 2004. CAL is also associated with targeting of other plasma membrane proteins such as Wnt receptors, Frizzled 5 and 8 (Yao et al, 2001), an EGF receptor family, CALEB/NGC (Hassel et al, 2003) and a chloride channel protein, ClC-3B (Gentzsch et al, 2003). It is supposed that CAL takes part in their intracellular trafficking, which was evidenced by interaction with a Q-SNARE protein, syntaxin 6 (Charest et al, 2001), and a small GTPase, TC10 regulating the translocation of the insulin-stimulated glucose transporter, GLUT4 to plasma membrane (Chiang et al, 2001;Neudauer et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…These results prompted us to conclude that ClC-3 may be a part of endogenous VRAC per se or, given the evidence on possible intracellular ClC-3 location (e.g. Li et al 2002, Gentzsch et al 2003, a part of the molecular machinery involved in VRAC activation/ regulation in LNCaP cells. Moreover, the fact that the elevation of endogenous levels of ClC-3 protein in response to NE-differentiating regimens was paralleled by the enhancement of I Cl,swell not only provided an additional strong argument for a causal link between ClC-3 expression and VRAC function, but also suggested that NE differentiation modulates I Cl,swell by affecting ClC-3 content.…”
Section: Ne Differentiation and Volume Homeostasismentioning
confidence: 99%